A high performance lithium-ion–sulfur battery with a free-standing carbon matrix supported Li-rich alloy anode. Issue 47 (28th September 2018) - Zhang, Tao; Hong, Min; Yang, Jun; Xu, Zhixin; Wang, Jiulin; Guo, Yongsheng; Liang, Chengdu
Abstract : A high-performance lithium-ion–sulfur battery has been built by using a carbon supported Li-rich alloy anode and sulfurized polyacrylonitrile (S@pPAN) cathode. Abstract : Although the lithium–sulfur battery exhibits high capacity and energy density, the cycling performance is severely retarded by dendrite formation and side-reactions of the lithium metal anode and the shuttle effect of polysulfides. Therefore, exploring lithium rich-alloy (or compound) anodes and suppressing the shuttling of polysulfides have become practical technical challenges for the commercialization of lithium–sulfur batteries. Here, a lithium ion sulfur full battery system combining a lithium-rich Li–Si alloy anode and sulfurized polyacrylonitrile (S@pPAN) cathode has been proposed. The free-standing CNF matrix supported Li–Si alloy anode is prepared by a simple and effective method, which is practical for scale-up production. The obtained Li–Si alloy anode demonstrates high cycling stability without dendrite growth, while the use of the S@pPAN cathode avoids the shuttle effect in carbonate electrolytes. The constructed Li–Si/S@pPAN battery could be cycled more than 1000 times at 1C and 3000 times at 3C, with a capacity fading rate of 0.01% and 0.03% per cycle. The exceptional performance should originate from the stable integrated anode structure and the excellent compatibility of the S@pPAN cathode and Li–Si alloy anode with carbonate electrolytes.